2016
DOI: 10.3390/molecules22010005
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities and Chemical Constituents of Flavonoids from the Flower of Paeonia ostii

Abstract: Paeonia ostii is a traditional medicinal plant popularly used in China. This study intended to evaluate the antioxidant properties and the chemical components of the flavonoid-rich extracts from the flowers of P. ostii. The results showed that the flavonoid-rich extracts from the flowers of P. ostii had strong scavenging capacities on 2,2′-Azinobis-(3-ethylbenzthiazoline-6-sulphonate) (ABTS), hydroxyls, superoxide anions, and 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals in a dose-dependent manner. Five flavon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 35 publications
5
42
0
Order By: Relevance
“…It is assumed that the content of phenolic and flavonoid compounds of the extract and Pd@W.tea NPs would afford them promising radical scavenging activity because these compounds are known to be scavengers of DPPH, OH, and NO. 25,31,32 The radical scavenging activities of white tea extract for DPPH was high even at low doses and was not dose-dependent (Figure 7). On the other hand, the DPPH scavenging activity of Pd@W.tea NPs was low at low concentrations and only began to approach antioxidation efficacy of white tea extract only after reaching high doses.…”
Section: Radical Scavengingmentioning
confidence: 97%
“…It is assumed that the content of phenolic and flavonoid compounds of the extract and Pd@W.tea NPs would afford them promising radical scavenging activity because these compounds are known to be scavengers of DPPH, OH, and NO. 25,31,32 The radical scavenging activities of white tea extract for DPPH was high even at low doses and was not dose-dependent (Figure 7). On the other hand, the DPPH scavenging activity of Pd@W.tea NPs was low at low concentrations and only began to approach antioxidation efficacy of white tea extract only after reaching high doses.…”
Section: Radical Scavengingmentioning
confidence: 97%
“…A recent study showed that the extracts from the flowers of P. ostii have numerous antioxidant properties and these properties are closely related to the high content of flavonoids (Zhang et al, ). Moreover, other studies suggested that the extracts from the root cortex of P. suffruticosa significantly reduced the cellular tyrosinase and DOPA oxidase activity as well as melanin content in B16 cells, which could be due to its abundant phenolic and flavonoid content‐induced antioxidant activities (Ding et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Eleven flavonoids were isolated and their structures were elucidated as chrysoeriol‐7‐ O ‐glucopyranoside (1), kaempferol‐7‐ O ‐glucopyranoside (2), dihydrokaempferol‐7‐ O ‐glucopyranoside (3), luteolin‐7‐ O ‐glucopyranoside (4), apigenin‐7‐ O ‐neohesperidoside (5), apigenin‐7‐ O ‐glucopyranoside (6), kaempferol‐3‐ O ‐glucopyranoside (7), apigenin (8), kaempferol (9), dihydrokaempferol (10), and peonin (11) (Wang et al, ; Zhang et al, ; Zhao et al, ). Among them, compounds 2 and 7 were abundant in the P. ostii flower and in flavonoid‐rich extracts (Zhang et al, ). We suspect that the flavonoid content of Pd and Po could include but not be limited to these contents, and it differs in different parts of the flower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Group 1, the diabetic control, was administrated 1 mL normal saline, group 2 was administered 1 mg/kg glibenclamide, and the other groups were administered ZSC-1, ZSC-2 and ZSC-3 at 250 and 500 mg/kg, respectively. The animals were loaded with glucose (3 g/kg) [11] and blood samples were collected immediately before drug administration and at 30, 60, 90 and 120 min after drug administration.…”
Section: Glucose Tolerance Testmentioning
confidence: 99%